ANALYSIS OF FINANCIAL DISTRESS DIFFERENCES IN HOSPITALS LISTED ON IDX PRE AND POST COVID-19 PANDEMIC - Agum Patriotama; Tri Bodroastuti; Wenny Ana Adnanti (Jurnal Akuntansi dan Bisnis, 2025)
The COVID-19 pandemic affected hospitals by reducing inpatient and outpatient volumes while increasing operational costs. This study analyzes financial distress differences in six private hospitals listed on the Indonesia Stock Exchange using the Altman Z”-Score and Springate models. A quantitative comparative method with purposive sampling was applied, using secondary data from 2018–2022, analyzed with the Paired Sample T-Test. Results show no significant differences in financial distress before and after COVID-19 (Altman Sig. 0.415; Springate Sig. 0.128). All hospitals remained in the safe zone, indicating financial stability throughout the pandemic.